(untitled) (Journal of Health, Population and Nutrition, 2010)
Although sexual and reproductive health education and services are provided to young people, current rates of HIV infection and pregnancy are increasing in Nepal, indicating that young people do not always use sexual health services. Health facilities have apparently failed to provide young people with specialized sexual health education and services. This study explored the barriers to using sexual health services, including condom-use among young people in Nepal. Participants from 10 focus groups and 31 in-depth interviews, carried out by a same-sex researcher, reported many socioeconomic, cultural and physical norms that impose barriers to accessing information on sexual health and relevant services. It is concluded that the establishment of youth-friendly service centres in convenient places might help encourage young people to use sexual health services. Key words: Barriers; Condom; Health education; Health services; Qualitative studies; Sex behaviour; Sexual health; Sexual health services; Nepal DOI: 10.3329/jhpn.v28i6.6611 J HEALTH POPUL NUTR 2010 Dec;28(6):619-627